Abitare la Sanità: l'altra faccia della città storica - Calderoni, Alberto; Freda, Gianluigi; Giammetti, Mariateresa (Teaching Architecture, 2021)
This volume presents the outcomes of the three third-year Design Studios conducted within the bachelor's degree program in Science of Architecture (Department of Architecture - University of Naples "Federico II"). The place chosen to situate the different design strategies developed by each course has been Sanità, a central area that developed as a periphery of the adjacent city centre, a major example of a logic of systematic fragmentation and discontinuity that seems to have affirmed as a principle of a way of urbanizing the urban tissue of the city of Naples. Through essays and projects, this volume illustrates the results of a didactic approach that is functional to the needs of an open and inclusive School of Architecture, seeking at the same time - in the personal expertise of each teacher - which methods, processes, and ways of teaching the project can delineate different cultural horizons in favour of a plurality of views on the architecture of the city